Junior High School Students' Interest in Science Learning: A Case Study - Kharismayani, Annisa Lea; Winarno, Nanang; Afifah, Ratih Mega Ayu; Tortop, Hasan Said (Indonesian Journal of Teaching in Science, 2024)
This research aims to analyze students' interest in learning science. The method used is a survey. Data collection techniques used interest questionnaires and interviews. The research was conducted on 409 junior high school students in Bandung, Indonesia, consisting of 201 male students and 208 female students. The research results show that students' interest in learning science is in the good enough level interest category. This research also identified factors that can influence students' interest in learning science in sequence. Five factors include teacher, family, informal learning experiences, learning experiences in the classroom, and friends. Analysis of students' interests based on gender was carried out using the Kruskall-Wallis Test. There is a difference in the average score of students between men and women, which shows that female student's interest in learning is higher. Based on student's responses to open questions and interviews, information was obtained that the reason they were interested in science was that science was material that had many practicum concepts that could be carried out, exciting learning activities, and support from parents at home. Meanwhile, the most dominant reasons they are not interested in science are the physics material, which contains a lot of calculations and the science teachers are not interesting.